Software Analytics as a Learning Case in Practice: Approaches and Experiences - Zhang, Dongmei; Dang, Yingnong; Lou, Jian-Guang; Han, Shi; Zhang, Haidong; Xie, Tao (MALETS 2011, 2011)
Software analytics is to enable software practitioners to perform data exploration and analysis in order to obtain insightful and actionable information for data-driven tasks around software and services. In this position paper, we advocate that when applying analytic technologies in practice of software analytics, one should (1) incorporate a broad spectrum of domain knowledge and expertise, e.g., management, machine learning, large-scale data processing and computing, and information visualization; and (2) investigate how practitioners take actions on the produced information, and provide effective support for such information-based action taking. Our position is based on our experiences of successful technology transfer on software analytics at Microsoft Research Asia.